Rapidly Self-Sterilizing PPE Capable of Destroying 100% of Microbes in 30-60 Seconds - Zinn, Alfred A.; Izadjoo, Mina; Kim, Hosan; Brody, Rachel L.; Roth, Robert R.; Vega, Agustin; Nguyen, Khanh K.; Ngo, Nhi T.; Zinn, Hannah T.; Antonopoulos, Nicholas; Stoltenberg, Randall M. (Frontiers in Cellular and Infection Microbiology, 2021)
The continued proliferation of superbugs in hospitals and the coronavirus disease 2019 (COVID-19) has created an acute worldwide demand for sustained broadband pathogen suppression in households, hospitals, and public spaces. In response, we have created a highly active, self-sterilizing copper configuration capable of inactivating a wide range of bacteria and viruses in 30-60 seconds. The highly active material destroys pathogens faster than any conventional copper configuration and acts as quickly as alcohol wipes and hand sanitizers. Unlike the latter, our copper material does not release volatile compounds or leave harmful chemical residues and maintains its antimicrobial efficacy over sustained use; it is shelf stable for years. We have performed rigorous testing in accordance with guidelines from U.S. regulatory agencies and believe that the material could offer broad spectrum, non-selective defense against most microbes via integration into masks, protective equipment, and various forms of surface coatings.